Efficacy and safety of the serratus anterior block compared to thoracic epidural analgesia in surgery: Systematic review and meta-analysis - Lusianawati; Christian Julio Suhardi; Christrijogo Sumartono; Citrawati Dyah Kencono Wungu (Tzu Chi Medical Journal)
Objectives: The objective of this study was to compare the efficacy and safety of serratus anterior plane block (SAPB) and thoracic epidural analgesia (TEA) in thoracic region surgery. Materials and Methods: We implemented a systematic search of PubMed, ScienceDirect, SCOPUS, and Web of Science and through gray literature for all randomized controlled trials that compared SAPB, a novel thoracic wall nerve block, and TEA in surgery. The evaluated outcomes included the Visual Analog Scale (VAS), hypotension, and postoperative nausea and vomiting (PONV). Review Manager, version 5.4.1, was implemented for the analysis of statistics. Results: The pooled analysis included six trials that fulfilled the inclusion criteria. In total 384, surgery had received regional blocks (162 – SAPB and 163 – TEA). VAS did not differ significantly between SAPB and TEA, with a mean difference of 0.71, P = 0.08. PONV incidence did not differ significantly between SAPB and TEA (odds ratio = 0.25, P = 0.07). Hypotension incidence was lower in SAPB compared to TEA (odds ratio = 0.10, P = 0.0001). Conclusion: SAPB yielded comparable VAS with TEA in pain management of thoracic region surgery. The incidence of hypotension was lower in SAPB than in TEA. No difference in PONV incidence was observed. SAPB can be a viable alternative to TEA in thoracic region surgery.